2021
DOI: 10.1002/ptr.7114
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐gastric cancer activity and mechanism of natural compound “Heilaohulignan C” isolated from Kadsura coccinea

Abstract: In this research, we analyzed the antitumor activity of one new compound Heilaohulignan C (B‐6) on the human gastric carcinoma cells. MTT, cell migration, Calcein AM/Propidium Iodide (PI), and flow cytometry in BGC‐823 cell line (gastric tumor). Western blot was utilized to distinguish the protein level. Xenografts nude mice were used for in vivo anticancer analysis. H&E staining and laboratory investigation was accomplished for toxicity study. MTT test demonstrated the cytotoxicity of BGC‐823 cells, Calcein A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Cytotoxicity was tested via 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay [ 18 ]. The cells transferred to 96-well plates (1 × 10 5 /well) were exposed to serum- and pyruvate-free medium.…”
Section: Methodsmentioning
confidence: 99%
“…Cytotoxicity was tested via 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay [ 18 ]. The cells transferred to 96-well plates (1 × 10 5 /well) were exposed to serum- and pyruvate-free medium.…”
Section: Methodsmentioning
confidence: 99%
“…Kadsura coccinea is an evergreen woody vine of the Schisandra genus in the Schisandra family, also known as cold rice ball, bufuna, chicken intestine wind, etc. Kadsura coccinea is an important medicinal resource, mainly distributed in Hunan, Guangxi, Guizhou, Fujian, and other places [ 1 ]. Folk medicine mostly uses its roots, vines, and fruits to treat stomach diseases, rheumatoid arthritis, bruises, swelling and pain, irregular menstruation, and so on [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Folk medicine mostly uses its roots, vines, and fruits to treat stomach diseases, rheumatoid arthritis, bruises, swelling and pain, irregular menstruation, and so on [ 2 ]. Pharmacological studies showed that Kadsura coccinea has the effects of antitumor [ 1 ], antioxidation [ 3 ], liver protection [ 4 ], and inhibition of acetylcholinesterase [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…calcein-AM (190,194,198,206,207), in which the acetylmethoxy methyl ester (AM) group enhances the hydrophobicity of the stain for easy penetration of the living cell membrane, is used to fluorescently label living cells. Next, calcein-AM is cleaved by intracellular esterases to yield highly fluorescent and polar calcein (208)(209)(210). When cells are incubated with calcein and co 2+ , both enter the cytoplasm; however, calcein is further captured by mitochondria (211,212).…”
Section: Detection Of Mitochondrial Permeability Transition Poresmentioning
confidence: 99%